The demand for news: Accuracy concerns versus belief confirmation motives - Felix Chopra; Ingar Haaland; Christopher Roth (University of Copenhagen, Department of Economics, Center for Economic Behavior and Inequality (CEBI), 2024)
We examine the relative importance of accuracy concerns and belief confirmation motives in driving the demand for news. In experiments with US voters, we first vary beliefs about whether an outlet reports the news in a right-wing biased, left-wing biased, or unbiased way. We then measure demand for a newsletter covering articles from this outlet. Right-wing voters strongly reduce their demand for left-wing biased news, but not for right-wing biased news. The reverse patterns hold for left-wing voters. These results suggest a trade-off between accuracy concerns and belief confirmation motives. We quantify this trade-off using a structural model and find a similar quantitative importance of both motives.
Keywords: D83; D91; L82; P00; 330; News Demand; Media Bias; Accuracy Concerns; Belief Confirmation